Examining the Impact of Cancel Culture and Culture Wars on Social Media - Ardiyanto, Erik; Utami, Atika Budhi; Masful, Mila Falma (Institut Komunikasi dan Bisnis LSPR, 2025)
Social media has become a significant platform for public communication, providing users with the freedom to express their opinions and engage in discussions. Through platforms like Twitter, individuals can easily access information and share their perspectives, leading to the rise of